Influence of method Thoracic-Abdominal Rebalance on parameters cardiorespiratory in patients with cystic fibrosis - Silva, Leandro Marques da; Monteiro, Elizângela de Sousa; Miranda, Bruno Silva; Silva, Clesio Rafael Lopes da; Costa, Anne Shirley Menezes (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Cystic fibrosis (CF) is a genetic, systemic disorder characterized by generalized dysfunction of exocrine glands, with chronic progressive evolution. The Thoracic-Abdominal Rebalancing (TAR) aims to encourage ventilation and promote the removal of pulmonary secretions. Objective: To evaluate the influence of TAR on cardiorespiratory parameters in CF patients. Method: This is an exploratory retrospective study of case series, which involved eight patients with CF, of both sexes, aged 3-24 years, who underwent TAR. Records of information was extracted on the identification, age, gender, time of diagnosis and general clinical status, as well as the data of the cardiorespiratory parameters: Heart Rate (HR), Respiratory Rate (FR), blood pressure (BP) and Saturation peripheral oxygen (SpO2), before and after each service. To compare the values, we used the parametric Student t test for paired samples, with statistical significance level of p = 0.05. Results: Male gender was prevalent in 62.5% of the sample analyzed. The mean age was 12.12 ± 7.20 years. The median time to diagnosis was around 10.11 ± 5.48 years. Comparing the total average values, verified a decrease of BP and HR variables after the completion of the TAR. However, no statistically significant difference, since there was obtained, respectively, p = 0.097 / p = 0.062. However, the RR showed a significant decrease (p = 0.012) and SpO2 (p = 0.030), which showed an increase after the implementation of the method. Conclusion: The TAR may influence the cardiorespiratory variables in CF patients, is showing to be a safe technique and of great importance in the treatment of these patients.